Removal of synthetic cationic dye from aqueous solution using date palm leaf fibers as an adsorbent - ., Shagufta; Dhar, Rahul; Kim, Bong-Sik; Alblooshi, Amani; Ahmad, Irshad (International Journal of Engineering and Technology, 2018)
An ecofriendly and economical adsorbent was studied as an alternative substitution of activated carbon for removal of synthetic dye from wastewater. Date palm leaf fibers were utilized as a biodegradable adsorbent to remove methylene blue dye from aqueous solution by ad-sorption. Several experiments were conducted to study the effect of adsorbent dosage, pH and dye concentration with time and we revealed that the adsorption percentage of methylene blue dye varied with these changes. The equilibrium adsorption data were analyzed by using Freundlich and Temkin isotherms and adsorption was found to well-fit into these two models. The equilibrium adsorption capacity (qe) increases with increasing the initial concentration of the dye and decreases with the adsorbent dosage and pH. The pseudo-second order kinetic model fits very well with the dynamic behavior of the adsorption of methylene blue dye on date palm leaf fibers under different ad-sorbent dosage, and dye concentrations. Based on the linearized correlation coefficient, the Freundlich equation is the best fit equilibrium isotherm for the sorption of methylene blue dye onto date palm leaf fibers. We can expect that in the future, date palm leaf fibers could be effectively used as an alternative to expensive adsorbents in the treatment of industrial wastewater containing synthetic dyes. Â Â